Thermophysical properties of some liquid binary Mg-based alloys - Plevachuk Y.; Sklyarchuk V.; Pottlacher G.; Yakymovych A.; Tkach O. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In this study, some structure-sensitive thermophysical properties, namely, electrical conductivity, thermal conductivity and thermoelectric power of liquid binary alloys Al33.3Mg66.7, Mg47.6Zn52.4 and Mg33.3Zn66.7 (all in wt.%), as the most promising cast alloys to fabricate components for cars, aircraft and other complex engineering products, were investigated. The electrical conductivity and thermoelectric power were measured in a wide temperature range by the four-point contact method. The thermal conductivity was measured by the steady-state concentric cylinder method. The obtained results are compared with literature experimental and calculated data.